One-Time Password Implementation on Lego Mindstorms NXT - Barlian Henryranu P; Heru Nurwarsito; Wijaya Kurniawan (Universitas Ahmad Dahlan, 2014)
One of the factors that affect the security of a network or system is user authentication and unfortunately at times it can be said not safe anymore. Brute force attacks on password systems are dominant (static) potential to penetrate network security or user authentication system. One way to overcome these drawbacks is to use the One Time Password (OTP) algorithm. OTP is a password security system using dynamic passwords. The password will be valid only for a session only, and so want to get into the next session, the password will be changed to the sequence/combination in accordance with certain rules or randomly determined by the user. In this research, author will be analyzed how the reliability of the OTP algorithm by applying it to a LEGO Mindstorm robot. The robot will be designed into a system where the user will be safe to enter the default password then the system will change the password every session. The results of the questionnaire showed that 81% users feel more secure, but more 60% said difficult to do because the user must perform the calculations in advance to enter the password.